NEW SELENATO TRIPHENYLTIN (IV) AND TRIMETHYLTIN (IV) DERIVATIVES: SYNTHESIS, INFRARED AND NMR STUDIES - WALY DIALLO (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2017)
Five derivatives of general formulae [cation] [SeO4SnR3] (R = Ph, Me) have been studied by infrared (IR) and nuclear magnetic resonance (NMR) spectroscopy. The suggested structures are infinite chains or oligomers, the environment around the tin centre being trans trigonal bipyramidal, the phenyl and methyl substituants occupying equatorial positions, the selenate anion behaving as a bridging bidentate ligand and occupying the apical positions. When cations are involved, supramolecular architectures may be obtained.